WIRELESS CHARGING METHOD FOR SMART CARD AND MOBILE DEVICE - SHIN, BYUNG KYOO; KWON, BIT NA; LEE, SOO HOON; JEUNG, YOUN PIL; HUR, GUK (2018)
The present invention provides a method for wirelessly charging a smart card through a mobile terminal, which charges a smart card by using a mobile terminal or a case of the mobile terminal. The method for wirelessly charging a smart card through a mobile terminal comprises the following steps of: performing a near field communication (NFC) with the smart card; selecting one of a charging mode including at least one of a simultaneous charging mode simultaneously charging the mobile terminal and the smart card, a real time charging mode, an automatic charging mode and one-time payment charging mode; and charging the smart card with the selected charging mode. 휴대 단말을 통해 스마트 카드를 무선 충전하는 방법은 스마트 카드와 근거리 무선 통신(NFC; near field communication)을 수행하는 단계, 휴대 단말과 스마트 카드를 동시에 충전하는 동시 충전 모드, 실시간 충전 모드, 자동 충전 모드 및 1회 결제용 충전 모드 중 적어도 하나를 포함하는 충전 모드 중 하나를 선택받는 단계 및 선택된 충전 모드로 스마트 카드를 충전하는 단계를 포함할 수 있다.